Durability and Cracking Defects in 3D-Printed Concrete - Gintautas Skripkiunas; Aigerim Tolegenova; Lyudmyla Rishko; Kenzhebek Akmalaiuly; Daiva Baltuškiene (Advances in Civil Engineering)
This article explores the durability and cracking defects associated with 3D-printed concrete, a rapidly emerging technology in construction. As the demand for innovative building techniques grows, understanding the long-term performance of 3D-printed structures becomes crucial. The most important properties of these products are the resistance to freezing and thawing and the possibility of cracking during maintenance. A fine-grained concrete mixture with expanded perlite additive was tested on strength, freezing–thawing resistance, and the reasons for cracking were analyzed during maintenance. Some differences between the results from standard concrete specimens and the results from 3D-printed concrete were obtained experimentally. During the research, 3D-printed concrete specimens were produced with industrial equipment, the density and compressive strength were determined, the mass loss of concrete specimens after freeze/thaw cycles was tested. By reducing the water-to-cement ratio to 11%, the strength of concrete with expanded perlite additive increased from 68.2 to 71.1 MPa. For concrete with W/C equal to 0.47 after 28 freeze/thaw cycles, the mass loss of 3D-printed specimens reaches 2.09 and 56 freeze/thaw cycles 9.17 kg/m2, and large surface defects were obtained. An analysis of the origin and recommendations for preventing cracks from occurring in 3D-printed products were carried out. The findings underscore the need for optimized mix designs and printing parameters to enhance durability.